Sintaksis dalam Membentuk Kalimat, Frasa dan Klausa Secara Lisan dan Tulis - Anggia Puteri; Jelice Twista Sijabat; Valentina Pinem; Esmeralda Sitohang; Violetta Olga Putri (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This article discusses the importance of syntax in forming sentences, phrases and clauses orally and in writing, but the author examines more about syntax in forming sentences. A sentence is the smallest unit of language that contains a complete message expressed orally or in writing. The method used is a qualitative approach based on literature which aims to examine the importance of syntax in forming sentences orally and in writing. The results of the study are then narrated in descriptive form. It can be concluded that the importance of syntax in forming sentences orally and in writing includes the nature of the sentence, syntactic function in basic sentences, derivative sentences (transformation sentences), classification of sentences based on (clause, predicate, and situational relationships), diathesis, and grammatical.